Finland : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper summarizes Nordea's operations and business model; the macroeconomic and prudential implications of the move; and policy responses taken so far. The IMF staff's assessment is that banking supervision in the euro area has improved significantly following the creation of the Single Supervisory Mechanism, which should mitigate potential risks from Nordea's move; meanwhile, the Nordic authorities have done much, in conjunction with the European Central Bank, to ensure that potential gaps and fragmentation across national jurisdictions are avoided. The resolution framework is designed to prevent taxpayers having to bail out banks, but is new, and work on building the crisis preparedness of euro area banks is still under way. The banking union is not yet complete, details of the backstop for the Single Resolution Fund need to be finalized and a common euro area deposit insurance should be made fully operational. At the same time, Nordea is also operating in non-euro area member states-maintaining cooperation between euro area and noneuro area institutions remains important.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet